Prenatal exposure to selenium may protect against wheezing in children by the age of 3. Issue 1 (11th December 2016) - Baïz, Nour; Chastang, Julie; Ibanez, Gladys; Annesi‐Maesano, Isabella
Abstract: Introduction: It has been suggested that human in utero exposure to heavy metals such as selenium can reduce the prevalence of childhood asthma and allergic diseases. However, data on this topic are scarce. The objective of the present study was to assess the putative associations between maternal selenium level during pregnancy and the risk of asthma, wheezing, allergic rhinitis, and atopic dermatitis in children from the EDEN birth cohort by the age of 1 and 3 years. Methods: Plasma selenium concentrations were measured in maternal blood during mid‐pregnancy (24–28 weeks of gestation) in 861 mothers. Cohort children were followed up from birth to 3 years using health questionnaires filled out by the parents for asthma, wheezing, allergic rhinitis, and atopic dermatitis. Maternal plasma selenium was related to the childhood outcomes by the age of 1 and 3 years. Results: Our results showed a significant negative association between a high maternal plasma selenium level during pregnancy and the risk of wheezing in the child by the age of 1 and 3 years. However, maternal plasma selenium during pregnancy was not associated with the prevalence of asthma, allergic rhinitis or atopic dermatitis. Conclusions: The results of this study suggest that the level of fetal exposure to maternal selenium could have an influence on the risk of wheezing in infancy and potentially on the risk of developing asthma later in life. Abstract : Studies showing protective role of maternal selenium during pregnancy are very few, whereas some studies found no effect of maternal selenium on asthma and allergic diseases. We confirmed in this study the protective role of maternal selenium against wheezing in young children under age of 3.